Inflammatory Bowel Disease Prevalence in Patients with Hidradenitis Suppurativa Using Prospective Symptom-Based Questionnaires and Fecal Calprotectin Testing - Niamh Kearney; Emily K. Pender; Rosalind Hughes; Collette McCourt; Graham Turner; Graham Morrison; Glen Doherty; Juliette Sheridan; Donal O’Kane; Brian Kirby (Dermatology and Therapy)
Abstract Introduction Hidradenitis suppurativa (HS) is associated with inflammatory bowel disease (IBD). Using healthcare databases, an estimated 2.1% of patients with HS have IBD. Prospective screening of patients with HS with IBD sign/symptom-based questions and fecal calprotectin (FC) has not been studied. Our aim was to evaluate the prevalence of IBD in HS and the utility of a sign/symptom-based questionnaire and FC testing. Methods All patients with HS attending two clinics were invited to participate. Information was collected on demographics, HS severity, and IBD risk factors. Fecal samples were returned by patients for calprotectin testing (≤ 50 μg/g = negative, 50–150 μg/g = borderline, ≥ 150 μg/g = positive). Results We recruited 150 patients including 124 women (82.7%) with a median age of 36 years and Hurley stage 2/3 disease (88.6%); 11 patients had established IBD (7.3%). Up to 44.7% of patients reported gastrointestinal symptoms. In 98 patients who returned a fecal sample for calprotectin measurement, 10 had previously diagnosed IBD (10.3%), 81 had a negative FC (82.7%), 13 had a borderline FC (13.3%) and 4 had a positive FC (4.1%). Among 4 patients with a positive result, 2 had known IBD (50%); 2 without established IBD were referred to gastroenterology and 1 had a negative endoscopy reporting an acute diarrheal illness at the time of their FC. The second patient was diagnosed with endoscopic and histologic Crohn’s disease. Conclusions We report an IBD prevalence of 8%, higher than previous studies. Routine IBD sign/symptom-based assessment is currently recommended. In our study, this would result in a referral rate of 44.7%. Among 88 FC tests in patients without established IBD, 1 patient was diagnosed with incident occult Crohn’s disease. At a number needed to screen (NNS) of 88, routine evaluation of all patients with HS with FC may be justified especially prior to the use of interleukin (IL)-17 antagonists.